Collagen Sequence Analysis Reveals Evolutionary History of Extinct West Indies Nesophontes (Island-Shrews). (4th June 2020) - Buckley, Michael; Harvey, Virginia L; Orihuela, Johanset; Mychajliw, Alexis M; Keating, Joseph N; Milan, Juan N Almonte; Lawless, Craig; Chamberlain, Andrew T; Egerton, Victoria M; Manning, Phillip L
Abstract: Ancient biomolecule analyses are proving increasingly useful in the study of evolutionary patterns, including extinct organisms. Proteomic sequencing techniques complement genomic approaches, having the potential to examine lineages further back in time than achievable using ancient DNA, given the less stringent preservation requirements. In this study, we demonstrate the ability to use collagen sequence analyses via proteomics to assist species delimitation as a foundation for informing evolutionary patterns. We uncover biogeographic information of an enigmatic and recently extinct lineage of Nesophontes across their range on the Caribbean islands. First, evolutionary relationships reconstructed from collagen sequences reaffirm the affinity of Nesophontes and Solenodon as sister taxa within Solenodonota. This relationship helps lay the foundation for testing geographical isolation hypotheses across islands within the Greater Antilles, including movement from Cuba toward Hispaniola. Second, our results are consistent with Cuba having just two species of Nesophontes ( N. micrus and N. major ) that exhibit intrapopulation morphological variation. Finally, analysis of the recently described species from the Cayman Islands ( N. hemicingulus ) indicates that it is a closer relative to N. major rather than N. micrus as previously speculated. This proteomic sequencing improves our understanding of the origin, evolution, and distribution of this extinct mammal lineage, particularly with respect to the approximate timing of speciation. Such knowledge is vital for this biodiversity hotspot, where the magnitude of recent extinctions may obscure true estimates of species richness in the past.